Caracterización del potencial energético de las radiaciones solares para calentamiento de hornos de pintura automotriz en la ciudad de Latacunga año 2013. Diseño de un sistema de calentamiento de hornos de pintura con el uso de energía solar. - Quiroz Erazo, José Lizandro (2013)
In the present investigation a theoretical and experimental study of the energy potential of solar radiation for heating furnaces painting in the city of Latacunga is performed, with the objective of which is research to be well used as an alternative for use in heating automotive paint ovens, proposing an efficient option with a simulated design and thus reducing environmental pollution caused by automotive paint ovens with traditional heating systems. The literature review includes all activities related to finding information on a topic previously written bounded and which meets and critically discussed, information retrieved and used. The test developed in which summary measures of variations in solar radiation under different conditions to obtain the energy potential of solar radiation in the city of Latacunga in 2013 and used in the design of a heating system paint ovens, and perform simulations on SOLIDWORKS software. In the research literature referred in consultation study of texts, journals, articles indexed for a consistent methodology, the level of Master in Energy Management was established. Data from measurements made are based on the fundamental research, which check the energy potential of the sun's rays as an alternative energy source for heating furnaces automotive paint in the city of Latacunga to help decrease environmental pollution.